The Discussion of the Draft Federal Law (Law Project)”On Normative Legal Acts in the Russian Federation” - Ludmila Ivanovna Antonova (Управленческое консультирование)
The second part of the article deals with the analysis of the draft Federal law “On normative legal acts”, concerning the preparation of the draft normative legal act, as well as the systematization and codification of legislation.